Golda [videorecording (Blu-Ray)] - Martin, Nicholas; Mirren, Helen; Cottin, Camille; Ashkenazi, Lior; Heuberger, Rami; Keinan, Rotem, 1979-; Benedeḳ, Devir, 1969-; Piercy, Ellie; Goodman, Henry, 1950-; Stoppard, Ed; Mafham, Dominic; Knoller, Ohad, 1976-; et al. (Decal, 2023)
On October 6th, 1973, under cover of darkness, on Israel's holiest day and during the month of Ramadan, the combined forces of Egypt, Syria, and Jordan begin a surprise attack on the Sinai Peninsula and the Golan Heights. Outnumbered and outgunned, Israel's only female Prime Minister, Golda Meir, confronts the immediate, clear, and present danger of a ticking timebomb that she hoped never to face. Surrounded, isolated, and frustrated by the infighting of her all-male cabinet, with little hope of rescue, one woman is in a race against time to save millions of lives on both sides of the conflict.